THE EFFECTIVENESS OF AUDIO HYPNOTHERAPY IN REDUCING POSTPARTUM DEPRESSION DURING NEW NORMAL - Rosyati Pastuty; Elita Vasra; Gustiana (OPI Napoli, 2023)
Background: Postpartum depression is a life-threatening mental health disorder and occurs in 10-15% of women. "Globally, the incidence of postpartum depression reaches 10-15%. There are few reports in countries such as Malta, Malaysia, Austria, Denmark and Singapore. While in other countries such as Brazil, South Africa, Taiwan, Korea, Italy, and Costa Rica, symptoms of postpartum depression are reported to be quite high". "Based the criteria of the Diagnostic and Statistical Manual of Mental Disorders, fourth edition (DSM-IV) and the Edinburgh Postnatal Depression Scale (EPDS). Audio hypnotherapy, which is the provision of positive suggestions delivered through MP3, is a method to reduce the level of postpartum depression. This study aims to determine the effectiveness of audio hypnotherapy in reducing postpartum depression during the new normal. Materials and Methods: This quasi-experimental study used a pretest-posttest design involving 60 postpartum mothers with a history of normal delivery at 2 Midwife's clinics in Palembang City and 1 Midwife's clinic in Aceh. Postpartum depression levels were assessed using the Edinburgh Postnatal Depression Scale (EPDS). Data analysis used Paired Samples Test to determine differences in postpartum depression levels before and after listening to Hypnotherapy audio. Results: There was a decrease in postpartum mothers' depression level after listening to hypnotherapy audio for ± 2 weeks. Depression incidence before giving audio hypnotherapy has a mean value = 11.15, while after giving audio hypnotherapy, it increases to 8.90, with P-value <0.05. Conclusion: Audio hypnotherapy therapy has proven to be effective in reducing the incidence of depression in postpartum mothers.